Extremely strong damped Lyα systems at high redshifts. (December 2020) - Telikova, K N; Balashev, S A; Noterdaeme, P; Krogager, J-K; Ranjan, A
Abstract: We present a spectroscopic analysis of seven Extremely Strong Damped Ly α systems at redshifts z = 2–3, obtained with the intermediate-resolution spectrograph X-shooter on the Very Large Telescope. For all systems we estimated column densities of the neutral atomic hydrogen HI, metal abundances and dust depletion. We firmly detected molecular hydrogen H2 in two systems in our sample; for the remaining systems we set a conservative upper limits on the H2 column densities. The properties of the obtained systems are in consistency with the sample of the Extremely Strong Damped Ly α systems available in the literature.